Predisposing factors for admission to intensive care units of patients with COVID-19 infection—Results of the German nationwide inpatient sample - Keller, Karsten; Farmakis, Ioannis T.; Valerio, Luca; Koelmel, Sebastian; Wild, Johannes; Barco, Stefano; Schmidt, Frank P.; Espinola-Klein, Christine; Konstantinides, Stavros; Münzel, Thomas; Sagoschen, Ingo; Hobohm, Lukas (Frontiers in Public Health, 2023)
Abstract Background Intensive care units (ICU) capacities are one of the most critical determinants in health-care management of the COVID-19 pandemic. Therefore, we aimed to analyze the ICU-admission and case-fatality rate as well as characteristics and outcomes of patient admitted to ICU in order to identify predictors and associated conditions for worsening and case-fatality in this critical ill patient-group. Methods We used the German nationwide inpatient sample to analyze all hospitalized patients with confirmed COVID-19 diagnosis in Germany between January and December 2020. All hospitalized patients with confirmed COVID-19 infection during the year 2020 were included in the present study and were stratified according ICU-admission. Results Overall, 176,137 hospitalizations of patients with COVID-19-infection (52.3% males; 53.6% aged≥70years) were reported in Germany during 2020. Among them, 27,053 (15.4%) were treated in ICU. COVID-19-patients treated on ICU were younger (70.0 [interquartile range (IQR) 59.0-79.0] vs. 72.0 [IQR 55.0-82.0] years, P<0.001), more of-ten males (66.3% vs. 48.8%, P<0.001), had more frequently cardiovascular diseases (CVD) and cardiovascular risk-factors with increased in-hospital case-fatality (38.4% vs. 14.2%, P<0.001). ICU-admission was independently associated with in-hospital death (OR 5.49 [95%CI 5.30-5.68], P<0.001). Male sex (OR 1.96 [95%CI 1.90-2.01], P<0.001), obesity (OR 2.20 [95%CI 2.10-2.31], P<0.001), diabetes mellitus (OR 1.48 [95%CI 1.44-1.53], P<0.001), atrial fibrilla-tion/flutter (OR 1.57 [95%CI 1.51-1.62], P<0.001) and heart failure (OR 1.72 [95%CI 1.66-1.78], P<0.001) were independently associated with ICU-admission. Conclusion During 2020, 15.4% of the hospitalized COVID-19-patients were treated on ICUs with high case-fatality. Male sex, CVD and cardiovascular risk-factors were independent risk-factors for ICU admission.